Analisis Titik Kritis Penjaminan Kualitas Benih Kelapa Sawit di Indonesia - Febrian Isharyadi; Biatna Dulbert Tampubolon; Bambang Prasetya; Nur Tjahyo Eka Darmayanti; Utari Ayuningtyas; Ary Budi Mulyono; Daryono Restu Wahono; Ellia Kristiningrum; Novin Aliyah; Rika Dwi Susmiarni; Nuri Wulansari (Pusat Penelitian Kelapa Sawit, 2022)
Oil palm seeds are a very important element in determining the yield of oil palm plantations. The use of quality oil palm seeds will provide maximum productivity. However, until now there is still a lot of use of llegitimate oil palm seeds, especially on smallholder plantations. Standardization is the right way to guarantee the quality of oil palm seeds through the determination of strict criteria in the selection process for the seeds planted. As the initial stage and the basis for developing standards, it is necessary to identify the critical point in the supply chain of oil palm seeds to consumers. So, this study aims to analyze the critical point of guaranteeing the quality of oil palm seeds in Indonesia, to guarantee the availability of quality oil palm seeds. This study uses a qualitative exploratory method to obtain data and information related to critical points in the supply chain of oil palm seeds from respondents consisting of producer, breeder, Government, and expert in the field of oil palm seeds. The results showed there were 5 (five) critical points in ensuring the quality of oil palm seeds in Indonesia, namely the production process, especially at the pollination stage, the breeding process, the certification process, the supervision process, and the knowledge of the planters, especially in smallholder plantations. The critical points are recommended as the basis for developing national standards in guaranteeing quality oil palm seeds for the realization of the Government's program to increase the productivity of oil palm plantations in Indonesia.